2010
DOI: 10.1016/j.jmb.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Small Outer Capsid Protein, Soc: A Clamp for Stabilizing Capsids of T4-like Phages

Abstract: Many viruses need to stabilize their capsid structure against DNA pressure and for survival in hostile environments. The 9 kDa outer capsid protein (Soc) of bacteriophage T4, which stabilizes the virus, attaches to the capsid during the final stage of maturation. There are 870 Soc molecules that act as “glue” between neighboring hexameric capsomers, forming a “cage” that stabilizes the T4 capsid against extremes of pH and temperature. Here we report a 1.9 Å resolution crystal structure of Soc from the bacterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
128
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(135 citation statements)
references
References 53 publications
(55 reference statements)
4
128
0
1
Order By: Relevance
“…6A). Residues 268-399 are inserted into the axial domain and form the "I domain," a protrusion on the outer surface of the capsid (40) (Fig. 6A).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…6A). Residues 268-399 are inserted into the axial domain and form the "I domain," a protrusion on the outer surface of the capsid (40) (Fig. 6A).…”
Section: Significancementioning
confidence: 99%
“…S12). However, it was reported that T4 Soc proteins form trimers around quasi-threefold axes and do not interact with the I domain of T4 major capsid proteins (40). The T4 Soc protein increases the stability of the T4 capsid (40), and it is possible that phi812 cement protein has the same function, even though it has a different location within the capsid.…”
Section: Significancementioning
confidence: 99%
“…Although many minor capsid proteins are not essential for infection in laboratory conditions (8)(9)(10)(11), they may have provided favorable properties for the survival of phage in hostile environments. For instance, the minor capsid protein Soc of phage T4 provides enhanced capsid stability (9).…”
mentioning
confidence: 99%
“…The auxiliary role of SCP in gammaherpesvirus capsid stabilization mirrors that of cementing proteins often found in dsDNA bacteriophages, such as the Soc protein in phage T4 (42,43) and the gpD protein in phage λ (44), as proposed previously for VP26 of HSV (45). In phage λ, the 11.4-kDa gpD forms a trimer and binds to capsid surface at quasi-and icosahedral threefold axes after capsid maturation; it stabilizes the capsid structure by fastening six gpE (the MCP) subunits from three neighboring capsomers (44).…”
Section: Discussionmentioning
confidence: 83%
“…These nonessential auxiliary proteins in phages "cement" adjacent MCPs to stabilize the mature capsid against extremes in pH and temperature as well as other factors in their hostile environment. They also help the thin capsid shell to withstand the pressure exerted by the packaged DNA (42,44,46,47). In gammaherpesvirus, it is conceivable that the cross-linking by hexon SCP would also fasten the MCP subunits in hexons and thus increase the overall stability of the capsid.…”
Section: Discussionmentioning
confidence: 99%